Prioritization of cancer therapeutic targets using CRISPR-Cas9 screens - Behan, Fiona M.; Iorio, Francesco; Picco, Gabriele; Gonçalves, Emanuel; Beaver, Charlotte M.; Migliardi, Giorgia; Santos, Rita; Rao, Yanhua; Sassi, Francesco; Pinnelli, Marika; Ansari, Rizwan; Harper, Sarah; et al. (Nature, 2019)
In a screen of 324 human cancer cell lines and utilising a systematic target prioritization framework, the Werner syndrome ATP-dependent helicase is shown to be a synthetic lethal target in tumours from multiple cancer types with microsatellite instability, providing a new target for cancer drug development.
Gesehen am 24.09.2019